In vitro Comparison of Adipogenic Differentiation in Human Adipose-Derived Stem Cells Cultured with Collagen Gel and Platelet-Rich Fibrin - Priyadarshini, Pallavi; Samuel, Soumi; Kurkalli, Basan Gowda; Kumar, Chethan; Kumar, Basavarajappa Mohana; Shetty, Nikhil; Shetty, Veena; Vishwanath, Karthik (Indian Journal of Plastic Surgery, 2021)
Background: Adipose-derived stem cells (ADSCs) are the most preferred cell type, based on their phenotypic characteristics, plasticity, and favorable immunological properties for applications in soft-tissue augmentation. Hence, the present in vitro study was aimed to evaluate the adipogenic differentiation potential of human ADSCs upon culturing individually with collagen gel and platelet-rich fibrin (PRF).Materials and methods: The collected lipoaspirate was used for establishing ADSCs using enzymatic digestion method. Then, the cells were analyzed for their morphology, viability, proliferation rate, population doubling time (PDT), colony-forming ability, cell surface markers expression, and osteogenic differentiation as biological properties. Further, ADSCs were evaluated for their adipogenicity using induction media alone, and by culturing with collagen gel and PRF individually for prospective tissue augmentation.Results: ADSCs were successfully established in vitro and exhibited a fibroblast-like morphology throughout the culture period. Cells had higher viability, proliferation potential and showed their ability to form colonies. The positive expression of cell surface markers and osteogenic ability confirmed the potency of ADSCs. The ADSCs cultured on collagen gel and PRF, individually, showed higher number of differentiated adipocytes than ADSCs grown with adipogenic induction medium alone.Conclusion: The extent of lipid accumulation by ADSCs was slightly higher when cultured on collagen gel than on PRF. Additional experiments are required to confirm better suitability of scaffold materials for soft-tissue regeneration.
Keywords: Adipose-derived stem cells; Collagen; Platelet-rich fibrin; Adipogenic differentiation; In vitro